2022
DOI: 10.1002/jia2.26024
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Joint Decision‐Making in Future Multipurpose Prevention Technology (MPT) Choice: Qualitative Findings on MPT Attribute Preferences from the CUPID Study (MTN‐045)

Abstract: Introduction Young women in sub‐Saharan Africa account for two‐thirds of all new HIV infections and face high rates of unintended pregnancy. Multipurpose prevention technologies (MPTs) are promising products under development that are designed to simultaneously prevent HIV and unintended pregnancy. Since MPTs will be used in the context of sexual relationships, ensuring acceptability and use requires understanding the role of male partners in MPT use decision‐making. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Effects of MPT use on fertility and product-related preferences to facilitate return to fertility were explored infrequently in the reviewed articles. This topic was largely examined within studies on nanofiber fabric and implants and constituted one of the attributes included in MTN 045/CUPID, which included vaginal film/inserts, vaginal ring, and oral tablets ( 24 , 29 , 31 , 42 , 45 ). Some end users expressed preferences for MPT products that allowed for flexibility in contraception administration or similarly noted that lack of flexibility in contraception coverage was a limitation of specific methods ( 31 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Effects of MPT use on fertility and product-related preferences to facilitate return to fertility were explored infrequently in the reviewed articles. This topic was largely examined within studies on nanofiber fabric and implants and constituted one of the attributes included in MTN 045/CUPID, which included vaginal film/inserts, vaginal ring, and oral tablets ( 24 , 29 , 31 , 42 , 45 ). Some end users expressed preferences for MPT products that allowed for flexibility in contraception administration or similarly noted that lack of flexibility in contraception coverage was a limitation of specific methods ( 31 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Across most studies, female participants revealed a preference for products that did not interfere with sex or sexual pleasure for their male partners ( 6 , 23 , 24 , 31 , 34 , 37 , 38 , 40 , 51 ). Consequently, participants were initially disinterested in products (ring, diaphragm, fabric) that would be inserted into the vagina, could potentially change vaginal dryness or wetness, or become dislodged during sex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations